Use of a Rigid Curved Laryngoscope for Removal of a Fish Bone in the Hypopharynx - Hiroshi Sakaida; Kazuki Chiyonobu; Hajime Ishinaga; Kazuhiko Takeuchi (Case Reports in Otolaryngology)
Foreign body ingestion is a commonly encountered clinical problem. In particular, sharp foreign bodies lodged in the esophagus or hypopharynx can cause complications and require urgent removal. Removal by flexible esophagogastroduodenoscopy or rigid esophagoscopy is the treatment of choice and has high success rates, but cases in which these methods are unsuccessful must be treated with an external incision. A 62-year-old man was referred for a fish bone lodged in the hypopharynx that could not be removed by flexible esophagogastroduodenoscopy. We removed the bone transorally using a specially designed rigid curved laryngoscope. Based on our experience, this method may have clear practical value due to advantages of a wide field of view and use of multiple rigid forceps. Indications may be limited, but this novel method may reduce the limitations of noninvasive removal of foreign bodies.